2023
DOI: 10.1186/s40798-023-00658-5
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Prevalence of Doping Among Elite Athletes: An Analysis of Results Generated by the Single Sample Count Method Versus the Unrelated Question Method

Rolf Ulrich,
Léa Cléret,
R. Dawn Comstock
et al.

Abstract: In 2011, a group of researchers investigated the 12-month prevalence of doping at the 13th International Association of Athletics Federations World Championships in Athletics (WCA) in Daegu, South Korea, and also at the 12th Pan-Arab Games (PAG) in Doha, Qatar. The prevalence of doping at each event was estimated using an established randomized response method, the Unrelated Question Model (UQM). The study, published in 2018, found that the prevalence of past-year doping was at least 30% at WCA and 45% at PAG.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Additionally, results from the more recent doping prevalence study in the Netherlands [32,33] were published in Balk et al [34]. Studies by Ulrich et al [35] and Petróczi et al [36] were conducted in the same settings (and with the same sample for one set of data) but using different IEM, whereas Ulrich et al [37] presents a reanalysis of the data reported in Petróczi et al [36]. Lastly, Pitsch [38] and Christiansen et al [39] report the same study.…”
Section: Overview Of Outputsmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, results from the more recent doping prevalence study in the Netherlands [32,33] were published in Balk et al [34]. Studies by Ulrich et al [35] and Petróczi et al [36] were conducted in the same settings (and with the same sample for one set of data) but using different IEM, whereas Ulrich et al [37] presents a reanalysis of the data reported in Petróczi et al [36]. Lastly, Pitsch [38] and Christiansen et al [39] report the same study.…”
Section: Overview Of Outputsmentioning
confidence: 99%
“…Authors of the remaining studies (k = 15) did not consider the potential impact of noncompliance with survey instructions. Notably, the two studies excluded for duplication of data [37,39] also consider noncompliance for Forced Response and Single Sample Count models, respectively.…”
Section: Noncompliancementioning
confidence: 99%
See 1 more Smart Citation